1998
DOI: 10.1021/jp982136d
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Belousov−Zhabotinsky Oscillation in Small Beads

Abstract: We examined chemical oscillations in the Belousov−Zhabotinsky (BZ) reaction with spherical ion-exchange resin beads (radius:  0.1−0.4 mm) loaded with a cationic catalyst, ferroin, in which no traveling wave appears and the oscillation is synchronized over individual beads. The period of the oscillation increases with a decrease in the size of the beads. Based on a theoretical consideration of the effect of the diffusion of active species through the surface of the bead reactor into the bulk aqueous solution, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 17 publications
0
53
1
1
Order By: Relevance
“…In our experimental system, D z % 0, since the catalyst is fixed on the ion-exchange membrane [5,8,9]. field in a simple manner, we replace D x r 2 x with Àcx.…”
Section: Discussionmentioning
confidence: 99%
“…In our experimental system, D z % 0, since the catalyst is fixed on the ion-exchange membrane [5,8,9]. field in a simple manner, we replace D x r 2 x with Àcx.…”
Section: Discussionmentioning
confidence: 99%
“…As is shown in section2.2.3, adroplet of Br 2 aqueous solution swims in am onoolein (MO) squalane solution, due to the brominating reactionofMO. [132] Moreover,b ifurcation in the modes of reaction can be observed. [23,24,124] Therefore, ad ropleto fB Z solution also obtains ad riving force in aM Os qualane solution.…”
Section: Introduction Of Nonlinear Chemical Reactionsmentioning
confidence: 99%
“…Maselko et al studied regular and irregular spatial wave behaviors in BZ reaction systems with ferroin catalyst of varying cation-exchange resin sizes and concentrations of the reaction solution. 20 Meanwhile, Yoshikawa et al reported how the oscillating frequency in a single particle relies on bead size with a similar experimental system to that presented in the study of Maselko et al 21 Kurin-Csörgei, Szalai, and Körös reported pattern formation in CO 2 gas free bromate-1,4-cyclohexanedione-ferroin oscillating reaction system. 22 The absence of gas production makes this system an attractive candidate for investigating chemical wave formation.…”
Section: Introductionmentioning
confidence: 75%